Carbon nanotube-reinforced polymer composites for biomedical applications - Mohd Nizar, Muhd Razali; Nurul Najwa, Ruzlan; Amirul Hakim, Sufian (Springer, 2024)
The utilization of carbon nanotube-reinforced polymer composites (CNT-RPCs) has been recognized as a significant breakthrough in the field of material science, owing to their exceptional amalgamation of characteristics. The incorporation of carbon nanotubes (CNTs) into a polymer matrix results in a composite material that combines the notable mechanical strength, electrical conductivity, and thermal stability exhibited by CNTs with the inherent flexibility of polymers. The process of integration leads to the development of improved composite materials that are suitable for a wide range of applications, and possess the ability to modify their properties according to specific application requirements. CNT-RPCs have established a distinct position within the field of biomedicine, specifically in the domains of bone implantation, tissue engineering, regenerative medicine, and drug delivery. These cells offer notable benefits including biocompatibility, electrical conductivity, and efficient drug distribution. Moreover, the incorporation of carbon nanotubes (CNTs) into polymers has demonstrated significant advancements in the fields of electronics, aerospace, and medicine. Cutting-edge modeling techniques utilizing deep learning are currently being implemented to enhance and optimize these composite materials. The present analysis provides an in-depth exploration of the advancement, attributes, and utilization of carbon nanotube-reinforced polymer composites (CNT-RPCs) in the field of biomedicine. Notably, recent advancements, obstacles, and prospects pertaining to this revolutionary material are emphasized.